Psychometric Properties of the Assertive Behavior Scale for a Sample of Adolescents in Makkah Region - Al-Hazzazi, Muhammad Yahya; Al-Ghamdi, Saleh Yahya (Journal of Educational and Psychological Sciences, 2025)
This study aimed to examine the psychometric properties of the Assertive Behavior Scale among a sample of adolescents in the Makkah region. The study was designed to develop a comprehensive scale to measure the level of assertive behavior in adolescents, with the goal of understanding, interpreting, and analyzing their behavior to enable appropriate future counseling interventions. The research adopted a descriptive-analytical approach to describe and analyze the psychometric characteristics of the scale. A purposive sample of 264 high school students, with an average age of 17.27 years, representing middle adolescence in Makkah, was selected. Exploratory factor analysis was conducted to extract the dimensions of the scale, with factor loadings ranging between 0.507 and 0.993, indicating strong correlations between the scale items and the identified dimensions. The overall Cronbach’s alpha coefficient for the instrument was 0.935, and the weighted Omega coefficient was 0.934, confirming the scale’s validity, reliability, and suitability for accurately measuring assertive behavior in adolescents. Based on the findings, the researcher recommended designing high-quality counseling programs aimed at developing assertive behavior, as acquiring such behavior forms a strong and independent foundation for adolescents to confidently face life challenges, achieve personal success, and engage positively with their communities.
Keywords: Psychometric Properties; Assertive Behavior